Challenges Facing Vocational Education Students in Jordan in Light of the Covid-19 Pandemic: An Empirical Study - Inas Ahmad Albado; Lafi Makhareez; Ma'aly Almazari; Zakaria Ahmed Atyat; Niveen Z. Halalsheh; Mamon Alzboun (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: This study aims to uncover the challenges faced by vocational education students in Jordan in light of the COVID-19 pandemic. Methods: A sample of 1200 newly joined students was selected from the Vocational Training Corporation in the central region of Jordan. A questionnaire was designed, consisting of two domains: challenges related to infrastructure and challenges related to students. The validity and consistency of the questionnaire were verified. Results: The findings indicate that the level of challenges facing the students is high, both at the infrastructure level and the students' level, with no statistically significant effect on gender. Practical training necessitates specific materials, tools, and instruments that cannot be adequately provided through distance education. Conclusions: The study recommends improving the infrastructure of the vocational training institution to enhance the quality of education and training. Additionally, there is a need to increase financial support for the institution to effectively implement vocational training programs. Lastly, a comprehensive review of educational policies is necessary.